1976
DOI: 10.1038/263471a0
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal or absent β mRNA in β0 Ferrara and gene deletion in δβ thalassaemia

Abstract: In patients with betao thalassaemia from Ferrara, beta globin mRNA sequences are either absent or structurally abnormal while in betao thalassaemia in Catania, beta globin mRNA sequences are present. In deltabeta thalassaemia there is a deletion of beta-like globin genes, while in betao Catania DNA, no beta globin gene deletion is detectable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

1977
1977
2001
2001

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(38 citation statements)
references
References 20 publications
2
36
0
Order By: Relevance
“…However, it is clear that it must be considerable, as cases of P-thalassaemia have been demonstrated due to defects at every possible level: gene deletion [2,3], transcription, post-transcriptional processing and inactive mRNA [3,4,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is clear that it must be considerable, as cases of P-thalassaemia have been demonstrated due to defects at every possible level: gene deletion [2,3], transcription, post-transcriptional processing and inactive mRNA [3,4,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studi~ (Ottolenghi et aL, 1976;Ramirez et al, 1976) have shown that at least a partial deletion of the 8-and ~-globin genes has occurred in (8 ~)°-tbalAg~PmiR since the plateau level of ~-globin cDNA hybridization is reduced in DNA of patients with this disease. The precise extent of this deletion could not be determined from these experiments.…”
Section: Introductionmentioning
confidence: 94%
“…Most often, there are decreased amounts of the specific globin messenger RNA which serves as a template for the synthesis of the affected globin chain (4)(5)(6). The messenger RNA deficit results from either globin gene deletions (7)(8)(9)(10) or transcriptional or post-transcriptional impairment of the expression of globin genes (11)(12)(13). Analysis of the hemoglobins synthesized in patients with thalassemia has not shown abnormalities in the primary structure of the globin chains (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%